2019
DOI: 10.1016/j.scitotenv.2018.12.415
|View full text |Cite
|
Sign up to set email alerts
|

Presence of bacteria and bacteriophages in full-scale trickling filters and an aerated constructed wetland

Abstract: Presence of bacteria and bacteriophages in full-scale trickling filters and an aerated constructed wetland. Stoten (2018),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 67 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…Little is known about the specific contribution per unit on the removal efficiency. However, not strong contribution of FIOs removal was observed after a pre-treatment stage being an underground septic tank (Purnell et al., 2016) and a primary sedimentation tank (Stefanakis et al., 2019). Therefore, the sand filtration unit must have increased the FIOs removal rates in case of Ottoson et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Little is known about the specific contribution per unit on the removal efficiency. However, not strong contribution of FIOs removal was observed after a pre-treatment stage being an underground septic tank (Purnell et al., 2016) and a primary sedimentation tank (Stefanakis et al., 2019). Therefore, the sand filtration unit must have increased the FIOs removal rates in case of Ottoson et al.…”
Section: Discussionmentioning
confidence: 98%
“…This improvement has resulted in energy savings (20–50%) while compared to CAS systems (Pronk et al., 2017) and other technologies such as membrane bioreactors (Purnell et al., 2016). Moreover, less area is required compared to CAS systems or other technologies such as trickling filters and constructed wetlands (Stefanakis et al., 2019). Those processes normally include primary treatment and in the case of CAS a secondary sedimentation tank after the biological treatment to separate sludge from the liquid bulk.…”
Section: Discussionmentioning
confidence: 99%
“…HF aerated wetlands for secondary treatment of domestic wastewater are capable of approximately four log unit removal of E. coli [71]. Stefanakis et al [75] studied the use of an aerated wetland for tertiary treatment, reporting final effluent concentrations for E. coli, Fecal Coliform, and Intestinal Enterococci of 41, 14, and 3 CFU/100 mL, which are all below the WHO guidelines for reuse of treated water in agriculture [76].…”
Section: Research Trendsmentioning
confidence: 99%
“…Pathogen removal processes in aerated wetland systems. Stefanakis et al [75] report the first assessment of bacteriophages in aerated wetlands, and attribute the correlation of bacteria and bacteriophages in the effluent to the role of phages as bacterial predators. What are the primary mechanisms of pathogen removal in aerated wetlands?…”
mentioning
confidence: 99%
“…Full-scale CWs have the advantage of providing real world results in comparison to implementation at micro or meso scales ( Brisson and Chazarenc, 2009 ) and several studies have demonstrated full-scale CWs can achieve more than 60% removal efficiency ( Sim et al., 2008 ; Vystavna et al., 2017 ; Ali et al., 2018 ). However, full-scale CW experiments infrequently use replication due to its cost ( Brisson and Chazarenc, 2009 ; Stefanakis et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%